EFFECT OF L-ARGININE AND INSULIN ON ADRENAL GLAND DAMAGED BY STREPTOZOTOCIN IN ALBINO RATS - Mahar, Yasmeen; Qamar, Aisha; Hidayat, Mariyah; Salman, Sahal; Chaudhry, Shire; Saeeduddin, Muhammad Fawad (Journal of Ayub Medical College Abbottabad, 2021)
Background: The adrenal gland is one of the major endocrine glands involved not only in different physiological functions, but also in response to stress This study was done to asses the effects of L-arginine and insulin on streptozotocin (STZ) induced adrenal gland damage in albino rats. Method: This laboratory based experimental study on animals was undertaken in the Anatomy department of Basic Medical Sciences Institute (BMSI), Jinnah postgraduate Medical Center (JPMC), Karachi, from February to March 2018. Forty adult, healthy male albino rats were placed into 4 groups (10 each). Group A was taken as control. Group B was given STZ. Group C and D were given STZ as in group B with insulin and L-arginine respectively. Absolute and relative weight of adrenal glands was measured at the end of the study. Tissues from adrenal glands were processed and stained with Haematoxylin and Eosin for the morphometric study. Results: The absolute as well as relative adrenal weight of animals was significantly raised in group B in comparison to control, although showed a significant recovery in group C and D animals when insulin and L-arginine were added to STZ. Haematoxylin and Eosin (H&E) stained sections of adrenal cortex of STZ treated Group B showed reduced width of zona glomerulosa, with increased width of zona fasciculata and zona reticularis when compared to control. The width of these zones of adrenal cortex recovered to a significant extent when group C and D tissue sections were compared with STZ- treated group B tissue sections. Conclusion: This study highlighted the protective effect of L-arginine on adrenal gland weight and histology in streptozotocin induced adrenal gland damage, which was comparable to insulin. Keywords: Streptozotocin; L-arginine; Adrenal gland; Insulin